The Conflicts of the Orang Rimba and the Jambi Malay Community: Reality and Resolutions - Harun, Hermanto; R H, Mustiah; Najib, Khairun (KnE Social Sciences, 2023)
Since the New Order, the lands and forests of the Orang Rimba have been used as locations for the transmigration program and HPH and HP-HTI projects, resulting in the livelihoods of the Orang Rimba being destroyed and triggering conflicts. This paper discusses the recurring and endless conflicts between the Orang Rimba and the Jambi Malay community. The enmity is the impact of deforestation and the transmigration program. The values of the Orang Rimba’s customary law and their religious beliefs have been eroded, forcing them to claim lands and forests as well as their products being for all. From this problem, it is believed that to obtain in-depth data, the main sources of this article are from field observations, intensive interviews, published journals, previous research reports, and print and online media reports relating to the conflicts involving the Orang Rimba. Keywords: Orang Rimba; conflicts; lands and forests